2023
DOI: 10.1111/ijpo.13067
|View full text |Cite
|
Sign up to set email alerts
|

Review of paediatric obesity and non‐alcoholic fatty liver disease—A focus on emerging non‐pharmacologic treatment strategies

Travis L. Piester,
Nitin Jagtap,
Rakesh Kalapala

Abstract: SummaryObesity in paediatrics has become one of the most serious public health concerns worldwide. Paediatric obesity leads to increased adult obesity and is associated with several comorbidities, both physical and psychological. Within gastroenterology, non‐alcoholic fatty liver disease (NAFLD) is now the most common cause of paediatric liver disease and the most common cause of liver transplantation in young adults. Treatment for NAFLD largely focuses on treatment of obesity with weight loss strategies. Unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…The increased ALT levels are a surrogate marker for NAFLD, which has now become the most frequent cause of chronic liver disease, both in children and adults, and predicts later development of diabetes and metabolic syndrome in adults ( 36 ). Lifestyle changes with a healthier diet, gradual weight loss, and increased physical activity seem to be the first-line treatment for this disease at present and several studies demonstrated the beneficial effect of weight loss on fatty liver disease ( 37 ). In a cohort of 117 Danish children with obesity, a 10-week “weight loss camp” induced a significant reduction in transaminase levels, without gender difference ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased ALT levels are a surrogate marker for NAFLD, which has now become the most frequent cause of chronic liver disease, both in children and adults, and predicts later development of diabetes and metabolic syndrome in adults ( 36 ). Lifestyle changes with a healthier diet, gradual weight loss, and increased physical activity seem to be the first-line treatment for this disease at present and several studies demonstrated the beneficial effect of weight loss on fatty liver disease ( 37 ). In a cohort of 117 Danish children with obesity, a 10-week “weight loss camp” induced a significant reduction in transaminase levels, without gender difference ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…School closures and other restrictions due to the COVID-19 pandemic upset the everyday routine of children and adolescents, resulting in changes in eating behaviors and physical activity. Several papers were reported during the pandemic, suggesting particular attention Obesity in children is a significant risk factor for cardiovascular and metabolic connected diseases [50], including hypertension, metabolic syndrome, insulin resistance, type 2 diabetes mellitus, hyperlipidemia, polycystic ovarian syndrome [51], non-alcoholic fatty liver infiltration [52], later-life kidney disorders [53], precocious puberty, and early accelerated growth [54]. There is a close relationship between obesity, hypertension, and COVID-19, which should be taken into consideration due to the long-term cardiovascular risk in children.…”
Section: Pediatric Obesity In the Covid-19 Eramentioning
confidence: 99%